Analisis Kemampuan Pemecahan Masalah Biologi Materi Perubahan Lingkungan Di Sman 4 Yogyakarta - Sugma; Tien Aminatun; Dina Ayu Kiswandini (Postgraduate, University of Mataram, 2023)
To solve problems accurately and focused, students must have problem solving skills. The purpose of this study was to evaluate class X students of SMA N 4 Yogyakarta in the even semester of the academic year. This study uses a descriptive quantitative research method. As a sample used simple random sampling. According to Polya, there are four indicators of problem-solving ability: Understanding the problem, preparing, implementing plans, and re-checking are steps that must be taken. On the topic of environmental change, the test instrument revealed that students' problem-solving abilities were in the high range. But if we look at each indicator separately, we can see that all four of them belong to a group. This is because students do not double-check their written answers and continue to doubt these answers. The non-test instrument study, on the other hand, the non-test instrument study found that students' problem solving abilities were very good. Based on these findings, it can be concluded that the students' overall problem solving abilities are of a high standard. Because research findings cannot be used with all materials, problem solving skills must be tested with different materials.